Embracing AI in travel and tourism industry / Ranee Atlas, Tina Stephen Enggong and Saifulrizan Norizan - Atlas, Ranee; Enggong, Tina Stephen; Norizan, Saifulrizan (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The term artificial intelligence (AI) has gained popularity throughout society. AI is defined as the simulation human intelligence processed by machines, particularly computer systems. Expert systems, natural language processing, speech recognition, and machine vision are examples of AI applications that contribute in various ways for the economic growth of the country. Because of its potential to spur economic growth and alter industries, AI is attracting interest on a global scale (Huang, Chao, del la Mora Velasco, Bilgihan, & Wei, 2022). The adoption of AI in the age of digital technology is crucial. Since its inception, it has given a variety of industries, including the hospitality industry, several opportunities and challenges. These days, the hospitality sector operates in a highly competitive climate that is replete with new technology, with clients who demand superior service, hence, adoption of AI is considered necessary when transforming innovation into a global economy. AI powered technologies have been developed with the potential to improve the economy by raising people's living standards (Allam, 2016; Koo et al., 2021; Limna et al., 2021). In order for the software to learn automatically from patterns or features in the data, AI combines massive amounts of data with quick, iterative processing and sophisticated algorithms. For example, modern technologies like AI and robotics are being used by the hospitality and tourism industries to improve customer service and experience (Goel, Kaushik, Sivathanu, Pillai, & Vikas, 2022).